Integrating Transcriptomic and Proteomic Data: IL‐27B as a Key Protein in the Development of Septic Cardiomyopathy—A Retrospective Study - Yifeng Mao; Qingqing Chen; Yongpo Jiang; Xijiang Zhang; Qin Si; Panpan Xu; Zhongheng Zhang; Cheng Zheng; Ronghai Lin (Immunity, Inflammation and Disease)
ABSTRACT Background Septic cardiomyopathy (SCM) is a potentially fatal complication of sepsis. In this study, transcriptomic and proteomic analyzes of serum samples from sepsis patients were conducted to uncover the underlying pathological mechanisms and identify potential therapeutic targets for SCM. Methods This retrospective, dual‐center study investigated the progression of sepsis to SCM in patients admitted to intensive care units. A total of 50 patients were enrolled and divided into two groups: sepsis with cardiomyopathy (25 cases) and sepsis without cardiomyopathy (25 cases). Co‐expression network analysis was employed to elucidate the biological significance of differentially expressed proteins. By integrating proteomic and transcriptomic data, molecular networks were constructed to visualize interactions among key molecules, aiming to enhance data interpretation and support the study's findings. Results Proteomic analysis identified 216 differentially expressed proteins (Fold change > 1.5, p‐value < 0.05) between the two groups. Transcriptomic analysis revealed two proteins, including Interleukin‐27 subunit beta (IL‐27B) and carbonic anhydrase, co‐downregulated in patients with septic cardiomyopathy. IL‐27B was associated with the immune response, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicated its involvement in the cytokine‐cytokine receptor interaction signaling pathway. Conclusion Comprehensive integrated transcriptomic and proteomic analyzes identified significant changes in protein expression associated with SCM, primarily associated with inflammation‐related pathways and amino acid metabolism. These findings provide new insights into the pathological mechanisms of SCM and highlight potential therapeutic targets for its treatment. Trial Registration The Clinical Research Ethics Committee of Taizhou Hospital of Zhejiang Province affiliated to Wenzhou Medical University approved this study, and written informed consent was given by all patients or their legal representatives. (NO.K20201110).